A method for preparing a hybrid aluminum electrolytic capacitor by impregnation
Through the method of vacuum impregnated core packing in stages, the problems of long impregnation time, insufficient and poor consistency of the hybrid aluminum electrolytic capacitors are solved, and more efficient and consistent impregnation effect is achieved, and the performance and production efficiency of the capacitor are improved.
Patent Information
- Application Number
- CN202411445960.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The conventional method for immersion preparation of hybrid aluminum electrolytic capacitors has problems such as long impregnation time, insufficient impregnation and poor consistency of impregnation effect.
The core pack is vacuum-impregnated from both ends by adopting a partial impregnation mode, first impregnating the dispersion liquid, the chemical liquid and the electrolyte. Through the first impregnation treatment and the second impregnation treatment, the impregnation liquid is completely fully and uniformly immersed in the core pack.
It greatly shortens the impregnation time, improves the impregnation efficiency and consistency, improves the performance of the capacitor, reduces leakage current, simplifies operation, and reduces production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of capacitors, and in particular to an impregnation preparation method for a hybrid aluminum electrolytic capacitor. Background Art
[0002] As a basic component in circuit design, capacitors are widely used. According to the different dielectrics used, capacitors can be divided into various types such as aluminum electrolytic capacitors, ceramic capacitors, film capacitors, tantalum capacitors, supercapacitors, etc. Among them, aluminum electrolytic capacitors have a large market share due to their high cost performance and high capacitance. Aluminum electrolytic capacitors can be divided into three categories: liquid capacitors, solid capacitors and solid-liquid hybrid capacitors. In recent years, solid-liquid hybrid capacitors have gradually become the darling of aluminum electrolytic capacitors because they combine the advantages of solid capacitors and liquid capacitors with their high capacity extraction rate, low ESR, high temperature resistance, long life, moisture resistance, vibration resistance and other advantages.
[0003] In the impregnation process of the traditional aluminum electrolytic capacitor core package, the core package of the capacitor to be impregnated is first dried, and then different impregnation devices and electrolytes are selected according to different materials and specifications of the device, and then they are placed in different impregnation screens respectively, and then the impregnation screens are completely immersed in a vacuum tank storing different electrolytes. During the impregnation process, positive and negative pressures are cyclically applied to achieve complete impregnation. After a period of impregnation, the excess electrolyte on the capacitor core package is taken out and absorbed, and finally the staff manually checks the impregnation effect. This impregnation method is complicated to operate, the impregnation time is long, the impregnation effect is difficult to grasp, and many machines are required, which greatly increases the production cost and labor cost. Therefore, the existing impregnation preparation method of hybrid aluminum electrolytic capacitors has defects such as long impregnation time, insufficient impregnation and poor consistency of impregnation effect, which makes the use of this technology very limited. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a hybrid aluminum electrolytic capacitor by impregnation to solve the following technical problems:
[0005] The existing impregnation preparation method of hybrid aluminum electrolytic capacitors has problems such as long impregnation time, insufficient impregnation and poor consistency of impregnation effect.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] A method for preparing a hybrid aluminum electrolytic capacitor by impregnation includes at least the following steps:
[0008] The corroded anode aluminum foil and cathode aluminum foil are soaked in citrate;
[0009] Placing the electrolytic paper between the anode aluminum foil and the cathode aluminum foil and winding them into a core package;
[0010] Immersing at least half of the volume of the core package from one end into the impregnation liquid for a first impregnation treatment, then inverting the core package, and immersing at least the remaining half of the volume of the core package from the other end into the impregnation liquid for a second impregnation treatment;
[0011] Drying the core package after the second impregnation treatment;
[0012] The dried core package is assembled with an aluminum shell and a leather plug and subjected to an aging treatment to obtain a hybrid aluminum electrolytic capacitor.
[0013] As a further solution of the present invention: the concentration of the citrate is 1-3 g / L, the temperature is 90-100° C., and the soaking time is 5-10 min.
[0014] As a further solution of the present invention: the impregnation liquid is at least one of a chemical forming liquid, a dispersion liquid and an electrolyte solution.
[0015] As a further embodiment of the present invention: the dispersion is an aqueous compound containing poly(3,4-ethylenedioxythiophene) / polybenzenesulfonate, the chemical forming liquid is an ammonium adipate-based chemical forming liquid or a boric acid-based chemical forming liquid, and the electrolyte includes at least one of ethylene glycol, γ-butyrolactone, N,N-dimethylformamide, cyclopentane sulfone, water, and polyethylene glycol.
[0016] As a further solution of the present invention: the first impregnation treatment and the second impregnation treatment adopt vacuum pressure impregnation, and the vacuum degree is -0.08-0.15MPa.
[0017] As a further solution of the present invention: the first impregnation treatment is performed for 5-30 minutes at a temperature of 40-90°C, and the second impregnation treatment is performed for 5-30 minutes at a temperature of 40-90°C.
[0018] As a further solution of the present invention: the drying temperature is 125-200° C. and the drying time is 60-120 min.
[0019] Beneficial effects of the present invention:
[0020] The present invention simplifies the impregnation steps, shortens the impregnation time, reduces the problems of insufficient impregnation and poor consistency of impregnation effect by treating the aluminum foil with citrate and impregnating the core package step by step with impregnation liquid. The hybrid aluminum electrolytic capacitor prepared by the present application can be widely used in home appliances, computers, servers, communication equipment, mobile phones, fast chargers, optoelectronic products, new energy, high-speed railways, aerospace, automobile industry, military industry and other fields. Specifically, the impregnation method provided by the present invention adopts a divided impregnation mode to sequentially impregnate the aluminum foil with a dispersion liquid, a chemical solution and an electrolyte to obtain a hybrid aluminum electrolytic capacitor. The impregnation process is divided into a first impregnation treatment and a second impregnation treatment. The first impregnation treatment and the second impregnation treatment are vacuum impregnated from both ends of the core package respectively, so that the impregnation liquid is easier to penetrate into the core package, greatly shortening the impregnation time, improving the impregnation efficiency and consistency, and improving the performance of the capacitor. Compared with the impregnation method of the core package once, it can ensure that the impregnation liquid is completely, fully and evenly impregnated into the core package after the first impregnation treatment and the second impregnation treatment, avoiding insufficient and uneven impregnation of the core package or residual impregnation liquid. At the same time, the difficulty of impregnation in batches is small, the impregnation time is reduced, and the efficiency of the core package impregnation due to time-consuming heating is avoided. The stability and consistency of the hybrid aluminum electrolytic capacitor product finally obtained are improved, and the leakage current of the hybrid aluminum electrolytic capacitor product can be greatly reduced.
[0021] By adopting the impregnation method of the present invention, the impregnation time for small-sized core packages (such as 8-12mm in diameter) can be shortened to 4-10min, and combined with the pressurization method, the impregnation time can be further shortened; for large-sized core packages (such as 16-18mm in diameter), step-by-step impregnation can be selected in the first impregnation treatment step, first impregnating one-third of the core package, and then impregnating two-thirds of the core package. In the second impregnation treatment step, the core package is inverted, and first impregnating one-third of the core package and then impregnating two-thirds of the core package. The impregnation time can be shortened to 20-30min, and combined with the pressurization method, the impregnation time can be further shortened, which can greatly improve the impregnation efficiency while ensuring the impregnation effect. By setting the first impregnation treatment and the second impregnation treatment, the core package is completely impregnated in a shorter impregnation time. The short impregnation time shortens the entire impregnation operation time, greatly reduces the operation cycle and operation cost, and significantly improves production efficiency.
[0022] (2) In this application, the aluminum foil after hydration treatment and before chemical formation is treated with citrate. Since the hydrated oxide film is thick, it is easy to block the micropores in the corrosion foil, resulting in capacitance loss. After the anodic oxidation, the surface of the hydrated oxide film is loose and porous, and residues are left, which constitute the surface defects of the oxide film, resulting in capacitance loss and increased leakage current. The hydrated aluminum foil is treated with citrate before chemical formation, which helps to dissolve the loose and porous outer layer of the hydrated oxide film and eliminate the defects. After the citric acid immersion treatment, the voltage increase rate during chemical formation is significantly increased, the chemical formation time is shortened, the chemical formation efficiency is improved, and electric energy is saved. In addition, the citrate ions help to increase the crystal content of the anodized film, increase the specific capacitance, and improve the performance of the capacitor. DETAILED DESCRIPTION
[0023] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] The preparation method of the hybrid aluminum electrolytic capacitor comprises the following steps:
[0026] The corroded aluminum foil after hydration treatment is immersed in a 2 g / L trisodium citrate deionized water solution at 95°C for 5 minutes, taken out and lightly rinsed with deionized water, and the corroded aluminum foil is cut to obtain an anode aluminum foil and a cathode aluminum foil, and then the anode aluminum foil, the cathode aluminum foil and the electrolytic paper are wound into a core package by a core package winding machine, wherein the electrolytic paper is between the anode aluminum foil and the cathode aluminum foil, and the length of the electrolytic paper is longer than the length of the overlapping part of the anode and cathode aluminum foils, to obtain a core package;
[0027] The positive lead and the negative lead of the core package are electrically connected to the positive and negative electrodes of the power supply respectively, a voltage is applied to the positive and negative electrodes of the core package, and half of the core package is immersed in the chemical forming liquid from one end of the core package, and the chemical forming repair treatment is performed for 10 minutes to complete the first impregnation treatment, and then the core package is inverted, and the other half of the core package is immersed in the chemical forming liquid, and the chemical forming repair treatment is continued for 10 minutes to complete the second impregnation treatment, wherein the voltage value applied to the positive and negative electrodes of the core package is 0.8 times the withstand voltage value of the anode aluminum foil, and the chemical forming liquid can be selected from the ammonium adipate chemical forming liquid in the prior art, the impregnation temperature is 50° C., and the vacuum degree is -0.09MPa;
[0028] The core package impregnated with the chemical liquid is subjected to a heating and drying treatment, the heating and drying temperature is 150°C, the drying time is 30 minutes, and then impregnated with the dispersion liquid according to the above method, wherein the dispersion liquid is a PEDOT / PSS aqueous dispersion liquid, the impregnation temperature is 50°C, the vacuum degree is -0.09MPa, the first impregnation treatment time is 8 minutes, and the second impregnation treatment time is 8 minutes;
[0029] The core package impregnated with the dispersion liquid is subjected to a heating and drying treatment, the heating and drying temperature is 150° C., the drying time is 30 min, and then the electrolyte is impregnated according to the above method, wherein the electrolyte comprises triethylamine, phthalic acid and adipic acid, the impregnation temperature is 50° C., the vacuum degree is -0.09 MPa, the first impregnation treatment time is 8 min, the second impregnation treatment time is 8 min, and then the core package is placed at a temperature of 150° C. and dried for 40 min to obtain an impregnated core package;
[0030] The impregnated core package is assembled with an aluminum shell and a leather plug to obtain a semi-finished capacitor, and the semi-finished capacitor is charged and aged. Voltages are applied at 0.5 times, 1 times and 1.2 times the rated voltage respectively for segmented aging treatment. The aging temperature is 125°C and the aging time is 120 minutes to obtain a hybrid aluminum electrolytic capacitor.
[0031] Example 2
[0032] The preparation method of the hybrid aluminum electrolytic capacitor comprises the following steps:
[0033] The hydrated corroded aluminum foil is immersed in a 2 g / L trisodium citrate deionized water solution at 95°C for 10 minutes, taken out and lightly rinsed with deionized water, the corroded aluminum foil is cut to obtain an anode aluminum foil and a cathode aluminum foil, and then the anode aluminum foil, the cathode aluminum foil and the electrolytic paper are wound into a core package by a core package winding machine, the electrolytic paper is between the anode aluminum foil and the cathode aluminum foil, and the length of the electrolytic paper is longer than the length of the overlapping part of the anode and cathode aluminum foils, so as to obtain a core package;
[0034] The remaining components and preparation method are exactly the same as those in Example 1.
[0035] Example 3
[0036] The preparation method of the hybrid aluminum electrolytic capacitor comprises the following steps:
[0037] In the step of impregnating the chemical liquid, the first impregnation treatment time is 12 minutes, and the second impregnation treatment time is 12 minutes;
[0038] In the step of impregnating the dispersion, the first impregnation treatment time is 10 minutes, and the second impregnation treatment time is 10 minutes;
[0039] In the step of impregnating the electrolyte, the first impregnation treatment time is 10 minutes, and the second impregnation treatment time is 10 minutes;
[0040] The remaining components and preparation method are exactly the same as those in Example 1.
[0041] Example 4
[0042] The preparation method of the hybrid aluminum electrolytic capacitor comprises the following steps:
[0043] In the step of impregnating the chemical liquid, the first impregnation treatment time is 15 minutes, and the second impregnation treatment time is 15 minutes;
[0044] In the step of impregnating the dispersion, the first impregnation treatment time is 15 minutes, and the second impregnation treatment time is 15 minutes;
[0045] In the step of impregnating the electrolyte, the time of the first impregnation treatment is 15 minutes, and the time of the second impregnation treatment is 15 minutes;
[0046] The remaining components and preparation method are exactly the same as those in Example 1.
[0047] Comparative Example 1
[0048] The preparation method of the hybrid aluminum electrolytic capacitor comprises the following steps:
[0049] The corroded aluminum foil after hydration treatment is directly cut to obtain anode aluminum foil and cathode aluminum foil, and then the anode aluminum foil, cathode aluminum foil and electrolytic paper are wound into a core package by a core package winding machine, wherein the electrolytic paper is between the anode aluminum foil and the cathode aluminum foil, and the length of the electrolytic paper is longer than the length of the overlapping part of the anode and cathode aluminum foils, to obtain a core package;
[0050] The remaining components and preparation method are exactly the same as those in Example 1.
[0051] Comparative Example 2
[0052] The preparation method of the hybrid aluminum electrolytic capacitor comprises the following steps:
[0053] In the step of impregnating the chemical liquid, the core package is completely immersed in the chemical liquid for 16 minutes;
[0054] In the step of impregnating the dispersion, the core package is completely immersed in the dispersion for 20 minutes;
[0055] In the electrolyte impregnation step, the core package is completely immersed in the electrolyte for 20 minutes;
[0056] The remaining components and preparation method are exactly the same as those in Example 1.
[0057] Comparative Example 3
[0058] The preparation method of the hybrid aluminum electrolytic capacitor comprises the following steps:
[0059] The corroded aluminum foil after hydration treatment is directly cut to obtain anode aluminum foil and cathode aluminum foil, and then the anode aluminum foil, cathode aluminum foil and electrolytic paper are wound into a core package by a core package winding machine, wherein the electrolytic paper is between the anode aluminum foil and the cathode aluminum foil, and the length of the electrolytic paper is longer than the length of the overlapping part of the anode and cathode aluminum foils, to obtain a core package;
[0060] In the step of impregnating the chemical liquid, the core package is completely immersed in the chemical liquid for 16 minutes;
[0061] In the step of impregnating the dispersion, the core package is completely immersed in the dispersion for 20 minutes;
[0062] In the electrolyte impregnation step, the core package is completely immersed in the electrolyte for 20 minutes;
[0063] The remaining components and preparation method are exactly the same as those in Example 1.
[0064] Performance Testing
[0065] 10 hybrid aluminum electrolytic capacitors of Examples 1-4 and Comparative Examples 1-3 were manufactured, and the capacitance (CAP), dissipation factor (DF), and equivalent series resistance (ESR) values of these 7 groups of products were tested at a frequency of 120 Hz, and the leakage current (LC) was tested at a voltage of 35 V. The test results are shown in Table 1;
[0066] Table 1 Performance test results of products in Examples 1-4 and Comparative Examples 1-3
[0067]
[0068] As can be seen from Table 1, the parameters of the above four embodiments of the capacitors prepared by the method of the present invention all meet the operating standards, and the impregnation liquid is evenly and fully distributed between the aluminum foil and the electrolytic paper. Therefore, the impregnation process of the hybrid aluminum electrolytic capacitor core group provided by the present invention is simple and convenient to operate, and the entire impregnation process can be completed in only 3.5 to 5 hours, which greatly shortens the impregnation time and improves production efficiency. The core group after impregnation treatment has good quality and meets the operating standards. Compared with the capacitors prepared by the methods of Comparative Examples 1, 2 and 3, the impregnation effect of the core package of the present invention is better within the same or shorter impregnation time, and the hybrid aluminum electrolytic capacitor product prepared by the impregnation method provided by the embodiment of the present invention has higher stability in parameters such as capacity (CAP), loss (DF), leakage current (LC) and equivalent series resistance (ESR), better product consistency, and smaller product leakage current (LC).
[0069] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A method for preparing a hybrid aluminum electrolytic capacitor by impregnation, characterized in that: At least the following steps are included: The corroded anode aluminum foil and cathode aluminum foil are soaked in citrate; Placing the electrolytic paper between the anode aluminum foil and the cathode aluminum foil and winding them into a core package; Immersing at least half of the volume of the core package from one end into the impregnation liquid for a first impregnation treatment, then inverting the core package, and immersing at least the remaining half of the volume of the core package from the other end into the impregnation liquid for a second impregnation treatment; Drying the core package after the second impregnation treatment; The dried core package is assembled with an aluminum shell and a leather plug and subjected to an aging treatment to obtain a hybrid aluminum electrolytic capacitor.
2. The method for preparing a hybrid aluminum electrolytic capacitor by impregnation according to claim 1, characterized in that: The concentration of the citrate is 1-3 g / L, the temperature is 90-100° C., and the soaking time is 5-10 minutes.
3. The impregnation preparation method of a hybrid aluminum electrolytic capacitor according to claim 1, characterized in that: The impregnation liquid is at least one of a chemical forming liquid, a dispersion liquid and an electrolyte.
4. The impregnation preparation method of a hybrid aluminum electrolytic capacitor according to claim 3, characterized in that: The dispersion is an aqueous compound containing poly(3,4-ethylenedioxythiophene) / polybenzenesulfonate, the chemical forming liquid is an ammonium adipate chemical forming liquid or a boric acid chemical forming liquid, and the electrolyte includes at least one of ethylene glycol, γ-butyrolactone, N,N-dimethylformamide, cyclopentane sulfone, water, and polyethylene glycol.
5. The method for preparing a hybrid aluminum electrolytic capacitor by impregnation according to claim 1, characterized in that: The first impregnation treatment and the second impregnation treatment adopt vacuum pressure impregnation, and the vacuum degree is -0.08-0.15 MPa.
6. The method for preparing a hybrid aluminum electrolytic capacitor by impregnation according to claim 5, characterized in that: The first impregnation treatment is carried out for 5-30 minutes at a temperature of 40-90°C, and the second impregnation treatment is carried out for 5-30 minutes at a temperature of 40-90°C.
7. The method for preparing a hybrid aluminum electrolytic capacitor by impregnation according to claim 1, characterized in that: The drying temperature is 125-200° C. and the drying time is 60-120 min.
Citation Information
Patent Citations
Manufacturing method for solid electrolyte aluminum electrolytic capacitor suitable for alternating current circuit
CN103280332A
A method for immersing and drying a high voltage solid electrolytic capacitor
CN109003843A